Enhancing adoption of a home-based exercise program for mild balance dysfunction: A qualitative study - Meyer, C.; Williams, S.; Batchelor, F.; Hill, Kylie (Human Kinetics Inc, 2016)
© 2016 Human Kinetics, Inc. Introduction: The aim was to identify barriers and opportunities facing community health physiotherapists in delivering a home-based balance exercise program to address mild balance dysfunction and, secondly, to understand the perspectives of older people in adopting this program. Method: Focus groups, written surveys, and data recording sheets were used with nine older people and five physiotherapists. Focus groups were audio taped, transcribed, and coded independently by two researchers. Results: Thematic content analysis was undertaken. Emerging themes were: engaging in preventive health (various benefits, enhancing independence); adoption of strategies (acceptable design and implementation feasibility); exercising in context (convenience, practicality, and safety); and broader implementation issues (program design, proactive health messages, and a solid evidence base). Conclusion: The views of older people and physiotherapists were sought to understand the adoption of a previously successful home-based program for mild balance dysfunction. Understanding the unique context and circumstances for individuals and organizations will enhance adoption.